Development expereinces in the Indian economy inter-state perspectives - Brahmanda, P R (Ed.); Indian Economic Association. Trust for Research and Development; Panchamukhi, V R (Ed.) (Delhi Bookwell, 2001)
The present volumes deals with the different aspects of the inter state perspectives of the development experiences in the Indian economy.This volume based upon the conference organised by the Indian Economic Association Trust for Research and development
Keywords: Economic development; Economics-India; Agriculture-Economic aspects; Economics policy